2014
DOI: 10.1142/s0217979214300217
|View full text |Cite
|
Sign up to set email alerts
|

The nonequilibrium quantum many-body problem as a paradigm for extreme data science

Abstract: Generating big data pervades much of physics. But some problems, which we call extreme data problems, are too large to be treated within big data science. The nonequilibrium quantum many-body problem on a lattice is just such a problem, where the Hilbert space grows exponentially with system size and rapidly becomes too large to fit on any computer (and can be effectively thought of as an infinite-sized data set). Nevertheless, much progress has been made with computational methods on this problem, which serve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 98 publications
1
14
0
Order By: Relevance
“…These studies have shown a favorable polynomial scaling with respect to the system's number of particles. Such findings are consistent across many fields [7][8][9][10][11][12]; despite system complexity in the underlying physics, much of observed behavior is compressed, i.e., the dominant dynamics is manifested in significantly lower dimensions. Compression arises also in the search over the quantum control landscape as a favorable scaling of control complexity [13,14].…”
Section: Introductionsupporting
confidence: 63%
“…These studies have shown a favorable polynomial scaling with respect to the system's number of particles. Such findings are consistent across many fields [7][8][9][10][11][12]; despite system complexity in the underlying physics, much of observed behavior is compressed, i.e., the dominant dynamics is manifested in significantly lower dimensions. Compression arises also in the search over the quantum control landscape as a favorable scaling of control complexity [13,14].…”
Section: Introductionsupporting
confidence: 63%
“…These encompass fundamental questions ranging from the dynamical properties of high-dimensional systems [10,11] to the exact ground-state properties of strongly interacting fermions [12,13]. At the heart of this lack of understanding lyes the difficulty in finding a general strategy to reduce the exponential complexity of the full many-body wave function down to its most essential features [14].In a much broader context, the problem resides in the realm of dimensional reduction and feature extraction. Among the most successful techniques to attack these problems, artificial neural networks play a prominent role [15].…”
mentioning
confidence: 99%
“…These ideas acquire a very special meaning in the context of the quantum many-body problem where one deals with datasets that are exponentially large. Sophisticated techniques have been developed to tackle this difficult challenge, such as compressing the data by using information theory and machine learning tools [1] very similar in spirit to algorithms to compress images and videos. In our case, datasets are comprised of all possible electronic configurations and cannot be stored in the memory of the largest supercomputer.…”
Section: Introductionmentioning
confidence: 99%
“…The probability distribution of the visible vectors is formulated by first introducing a joint probability distribution for pairs of visible and hidden vectors from an energy function and Boltzmann weighting. Finally, the probability distribution for visible vectors is taken to be the sum of the joint probability distribution over all possible configurations of the hidden vectors: Carleo and Troyer [9] introduced a variational wavefunction for a spin- 1 2 system of N sites, which is inspired by the functional form of RBM. The visible layer corresponds to the spin configurations σ z = (σ z 1 , σ z 2 , · · · , σ z N ).…”
Section: Introductionmentioning
confidence: 99%